2017
DOI: 10.1097/hco.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of aortic valvular disease

Abstract: Purpose of Review Aortic valve disease is relatively common and encompasses both congenital and acquired forms. Bicuspid aortic valve (BAV) is the most common type of cardiac malformation and predisposes to the development of calcific aortic valve disease (CAVD). Since the description of the link between NOTCH1 and BAV and CAVD approximately a decade ago, there have been significant advances in the genetic and molecular understanding of these diseases. Recent findings Recent work has defined the congenital c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 51 publications
(59 reference statements)
1
9
0
Order By: Relevance
“…Specifically, mutations in NOTCH1 and GATA5 , have been associated with bicuspid aortic valve in humans. 21, 22 Consistent with findings in humans, dilation of the aorta has been reported in murine models with mutation of Notch1 , consistent with a role for Notch1 signaling in the development of the ascending aortic wall. 23, 24 Notch1 along with other genes are known to be important for the development of the aortic valve and ascending aorta, and it has been proposed that genetic abnormalities that result in BAV may also result in histopathologic changes, which predispose to aneurysm development.…”
Section: Discussionsupporting
confidence: 81%
“…Specifically, mutations in NOTCH1 and GATA5 , have been associated with bicuspid aortic valve in humans. 21, 22 Consistent with findings in humans, dilation of the aorta has been reported in murine models with mutation of Notch1 , consistent with a role for Notch1 signaling in the development of the ascending aortic wall. 23, 24 Notch1 along with other genes are known to be important for the development of the aortic valve and ascending aorta, and it has been proposed that genetic abnormalities that result in BAV may also result in histopathologic changes, which predispose to aneurysm development.…”
Section: Discussionsupporting
confidence: 81%
“…Previous studies hypothesized that EndoMT may also play a role in the pathogenesis of BAV. Additionally, genes involved in this process such as NOTCH1, TGFBR2 , and SMAD6 , have been found to cause BAV in mouse models, as well as being linked to BAV in human studies (Garg et al, 2005 ; Girdauskas et al, 2011b ; Tan et al, 2012 ; Andelfinger et al, 2016 ; Gillis et al, 2017 ; Koenig et al, 2017 ). Mice with Notch1 missense alleles have been characterized with multiple outflow tract and EndoMT defects (Koenig et al, 2015 ).…”
Section: Notch1 Signaling In Taamentioning
confidence: 99%
“…Combining pathological characterization of the leaflets following resection with network-based analysis of the proteomic and transcriptomic data has yielded new insight into the potential molecular drivers of aortic valve disease. Coupled with new genome wide association studies that have revealed new lipid associations with aortic valve disease, these big data approaches may provide new clues about points of non-invasive therapeutic intervention and the development of drug-based therapies (58, 59). However, challenges remain in identification of patients during the early stages of disease before gross remodeling of the aortic valve leaflets necessitate replacement.…”
Section: Valve Disease and Valve Repair And Replacement Technologiesmentioning
confidence: 99%